Microstrip antenna with two elements and defected ground structure for 5G mobile applications at 28/38GHz - Al Gburi, Ahmed Jamal Abdullah; Thakur, Ekta; Gupta, Anupma; Abdulhameed, Muhannad Kaml; Khaleel, Aymen D. (The Electromagnetics Academy, 2024)
A new type of compact line-fed MIMO antenna for 5G wireless communication is presented in this paper. A rectangular microstrip patch antenna with an inset feed is designed for the 28GHz and38GHzbands. T-shapedpatchcontainsinvertedI-shapedslots, providing a dual-band response at 28GHzand38GHz. ByintegratingtwoT-shapedpatches, theMIMO(MultipleInputMultipleOutput) antenna significantly improves signal diversity and data throughput, making it highly suitable for modern wireless applications such as 5G networks. Slot-formed defected ground structures (DGSs) are inserted into a partial rectangular ground plane. To fit into handset devices for the upcoming 5G mobile revolution, the antennas are modestly configured on a substrate measuring 14×28mm2, occupying minimal area and reducing mutual coupling. The ECC, MEG, TARC, and radiation efficiency values obtained from the antenna systems are suitable for 5G mobile applications, with excellent reflection coefficient characteristics.